Impact of Innovative Brand Experience on Brand Loyalty: Mediating Role of Brand Love - ur Rehman, Saif (South Asian Review of Business and Administrative Studies (SABAS), 2020)
Purpose: The aim of study is to observe the impact of innovative brand experience on brand love, which in turn influences their brand loyalty in airline sector of Pakistan. The study also examines the comparison between PIA and another airline brand which are operated in Pakistan. Methodology: Data was collected via self-administrative questionnaire from 505 passengers of different airline brands who have travelled before in airlines. SPSS and Amos versions 21.0 were used to analyze the measurement and structural models. Findings: The research examined that in airline sector of Pakistan role of innovative brand experience and airline service qualities have impact on brand love which develop the satisfaction and element of brand loyalty in consumer’s mind and it also help to pay premium price for their beloved brand. Moreover, in comparison of PIA and other airline brands there are difference in results of innovative brand experience and AIRQUAL’s impact on brand love. Limitations and Future Work: This research is conducted in Pakistan only; there should be conduct a research between Pakistan and other emerging countries which will give a better result for proposed model. Moreover, comparative study can be conducted between PIA and other airline brands which are operating domestically. Originality/ Value: This study is showing the mediating role of brand love between innovative brand experiences, AIRQUAL as independent variable and brand loyalty, willingness to pay price premium as dependent variable which was not discussed before like this. This study is given a detailed comparison between PIA and other airline brands in airline industry of emerging countries like Pakistan.